Ambiente organizacional y su influencia en la responsabilidad social de los empleadores de la Sociedad Schuldt Vizuete en Babahoyo - Alvarado Onofre, Emely Valentina (2021)
The present case study is the result of the thematic approach on the organizational environment and how it influences the social responsibility of the employers of the Schuldt Vizuete Society, the same, at present, has gained greater importance and form a relevant part at the time of doing business. The purpose of this research is to determine the close relationship between the variables organizational environment and social responsibility. The different concepts of several authors analyzed help us to deduce that the organizational environment must be part of the company since it is a social commitment to its employees to provide them with an environment conducive to their performance and thus contribute positively to their quality of life. Nowadays, the goals of an organization are not only based on generating profits, but also on working internally on organizational behavior, for a good coexistence among all employees. This was done through descriptive research, which revealed the details of the variables studied, using a questionnaire of eight questions that reveal the deficit within the organization. Finally, it was established that if the Schuldt Vizuete Society considers this research as a guide and seeks to put it into practice through training that orients them, it will greatly improve the problems already exposed.